STRATEGI PEMBENTUKAN KARAKTER SISWA MELALUI BUDAYA KEBERSIHAN PAGI DI SMP NEGERI 3 PANYABUNGAN - Musa, Faisal; Sarah Fitri; M. Alawi; Tri Pratiwi; Yuspa; Adelina; Nur Asiah; Nur Aisah; Ummu Salamah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the implementation of morning hygiene culture in instilling character education of discipline and responsibility in students and educational staff at SMP Negeri 3 Panyabungan. Morning hygiene culture is a routine activity carried out before the learning process begins through class assignments, cleaning the school environment, and supervision by teachers. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that the implementation of morning hygiene culture contributes to forming discipline through compliance with school schedules and regulations and forming a character of responsibility through carrying out tasks regularly and consistently. Supporting factors include the commitment of the principal and teachers, while the obstacle faced is the lack of awareness of some students in carrying out cleaning tasks. Morning hygiene culture is effective in supporting the strengthening of character education in schools.